ERCP with the overtube-assisted enteroscopy technique: a systematic review - Skinner, Matthew; Popa, Daniel; Neumann, Helmut; Wilcox, C. Mel; Moenkemueller, Klaus (Endoscopy, 2014)
Overtube-assisted enteroscopy (OAE) techniques have increased the ability to perform endoscopic retrograde cholangiopancreatography (ERCP) in patients with altered upper gastrointestinal anatomy, such as Roux-en-Y gastric bypass. The aim of this study was to compare the efficacy and safety of OAE-ERCP in patients with different configurations of upper gastrointestinal anatomy.A systematic review was performed following a literature search for papers published between 1966 and August 2013. The following databases were searched: MEDLINE (via PubMed), Embase, Cochrane library, and Scopus. The following end points were analyzed: diagnostic and therapeutic success rates, cannulation success rate, ERCP success rate, type of enteroscopy, types of intervention, complications.A total of 23 relevant reports on OAE procedures, including single-balloon, double-balloon, and spiral enteroscopy, were analyzed. Studies included a total of 945 procedures in 679 patients (age 2 - 91 years) who had a variety of postsurgical upper gastrointestinal anatomical configurations. Among patients who underwent Roux-en-Y with gastric bypass, endoscopic success was 80 % and ERCP success was 70 %. In patients who had undergone a Roux-en-Y with either a pancreaticoduodenectomy, pylorus-preserving pancreaticoduodenectomy, or hepaticojejunostomy, endoscopic success was 85 % and ERCP success was 76 %. In patients who had undergone a Billroth II procedure, endoscopic success was 96 % and ERCP success was 90 %. In patients with native papilla who underwent successful endoscopy, cannulation was successful in 90 % of patients compared with 92 % in patients with an anastomosis. Overall ERCP success for all attempts was approximately 74 %. Interventions included sphincterotomy, pre-cut papillotomy, anastomotic stricturoplasty, stone removal, stent insertion, stent replacement, and balloon dilation of stenotic anastomosis. There were 32 major complications among the 945 procedures (3.4 %).Both endoscopic and ERCP success rates were highest in patients with Billroth II anatomy, followed by those with pancreaticoduodenectomy and Roux-en-Y hepaticojejunostomy; the lowest success rates were in patients with Roux-en-Y gastric bypass. Cannulation rates appeared to be equivalent in patients with both native papilla and biliary-enteric or pancreaticoenteric anastomoses. The diagnostic and therapeutic potential of balloon-assisted ERCP were high and the adverse event rate was low.
EVALuna2:1892